PELATIHAN BUDIDAYA DAN RANCANG BANGUN MESIN MULTIFUNGSI (PENGADUK, PENCACAH, DAN PENCETAK PELET) IKAN AIR TAWAR DAN AYAM KAMPUNG - Abdul Gafur; Endang Sri Wahyuni (JUARA: Jurnal Wahana Abdimas Sejahtera, 2020)
The purpose of the Implementation of Appropriate Technology Application Program (PPTTG) is to help overcome community problems in Desa Pambang Baru especially the Blessing Farmers Group to overcome the high price of native chicken and freshwater fish feed. In addition, the results of this technology can utilize unused waste into high selling prices and can be used by farmers as cheap and affordable feed. Expected outputs from the Appropriate Tenology Application Program (PPTTG) include the formation of a joint business group (KUBE) in Desa Pambang Baru in commercial commercial poultry and freshwater fish pellet business. Stages of activities to be carried out in the form of procurement/manufacture of Penepung machines, mixer and pellet machines as well as training and workshops for native chicken and freshwater fish farming.The results of this service activity created a set of pellet processing equipment, ranging from flour, stirring and pellets as well as the implementation of training and workshops on cultivation and post-harvest native chicken and freshwater fish. With the community service activities and the appropriate technology that is applied can increase the income of farmers and can help reduce the price of feed that is too expensive